I need to evaluate this integral: $\int_0^1 \frac{\log(x+1)}{1+x^2} dx$.

I've tried $t=\log(x+1)$, $t=x+1$, but to no avail. I've noticed that:

$\int_0^1 \frac{\log(x+1)}{1+x^2} dx = \int_0^1\log(x+1) \arctan'(x)dx =\left. \log(x+1)\arctan(x) \right|_{x=0}^{x=1} - \int_0^1\frac{\arctan(x)}{x+1}dx$

But can't get further than this.

Any help is appreciated, thank you.


Going a little round-about way. Consider, for $ s \geqslant 0$, a parametric modification of the integral at hand: $$ \mathcal{I}(s) = \int_0^1 \frac{\log(1+s x)}{1+x^2} \mathrm{d} x $$ The goal is to determine $\mathcal{I}(1)$. Now: $$ \begin{eqnarray} \mathcal{I}(1) &=& \int_0^1 \mathcal{I}^\prime(s) \mathrm{d} s = \int_0^1 \left( \int_0^1 \frac{x}{1+s x} \frac{\mathrm{d} x}{1+x^2} \right) \mathrm{d} s \\ &=& \int_0^1 \left.\left( - \frac{1}{1+s^2} \log(1+s x) + \frac{s}{1+s^2} \arctan(x) + \frac{1}{2} \frac{\log(1+x^2)}{1+x^2} \right) \right|_{x=0}^{x=1} \mathrm{d} s \\ &=& \int_0^1 \left( \color\green{ -\frac{\log(1+s)}{1+s^2}} + \frac{1}{4} \frac{\pi s+\log(4)}{1+s^2}\right) \mathrm{d} s = - \mathcal{I}(1) + \frac{1}{4} \pi \log(2) \end{eqnarray} $$ Hence $$ \mathcal{I}(1) = \frac{\pi}{8} \log(2) $$

  • 1
    $\begingroup$ This seems like a great solution, but I'll need to take some time to properly "digest" it (I've never seen this technique so far, and I want to make sure I properly understand what happens) $\endgroup$ – Gabi Purcaru Jul 18 '12 at 8:58

Here's a solution that uses simpler tools (or at least tools that I'm more familiar with):

$I =\int_0^1\frac{\log(1+x)}{1+x^2} dx $. We change $x$ into $x=\tan(t)$. Then $t=\arctan{x}$, $dt=\frac{1}{1+x^2}dx$, and the integral becomes:

$I = \int_0^{\frac{\pi}{4}}\log(1+\tan(t))dt$. Now $s = \frac{\pi}{4}-t$, $ds=-dt$, and the integral becomes:

$I = -\int_{\frac{\pi}{4}}^0 \log(1+\tan(\frac{\pi}{4}-s))ds = \int_0^{\frac{\pi}{4}} \log(1+\tan(\frac{\pi}{4}-s))ds$

Using $\tan(a-b) = \frac{\tan a - \tan b}{1 + \tan(a)\tan(b)}$, we have

$I = \int_0^{\frac{\pi}{4}} \log(1+\frac{1 - \tan s}{1 + \tan s}) ds = \int_0^{\frac{\pi}{4}}\log(\frac{2}{1+\tan s}) ds = \int_0^{\frac{\pi}{4}} (\log(2) - \log(1+\tan s)) ds = \int_0^{\frac{\pi}{4}}\log(2)ds - I = \frac{\pi}{4}\log(2) - I$.

So $I = \frac{\pi}{4}\log(2) - I$, hence $I = \frac{\pi}{8}\log(2)$.



$$I(a)=\int_0^1 \frac{\log(1+ax)}{1+x^2}dx$$

Differentiate it, to get

$$I'(a)=\int_0^1 \frac{x}{(1+ax)(1+x^2)}dx$$

Integrate that rational function, then integrate w.r.t. $a$ and find $I(a=1)$.

As Theorem suggested, you can also do the following:

$$\int_0^1 \frac{\log(1+x)}{1+x^2}dx$$

$$\int_0^1 \left(\int_0^x \frac{1}{1+y}dy\right)\frac{1}{1+x^2}dx$$

$$\int_0^1 \int_0^x \frac{1}{1+y}dy\frac{1}{1+x^2}dx$$

Now make a change of variables $y=ux$ in the inner integral:

$$\tag 1 \int_0^1 \int_0^1 \frac{x}{1+ux}\frac{1}{1+x^2}dudx$$

Now partial fractions:

$${x \over {1 + xu}}{1 \over {1 + {x^2}}} = {1 \over {1 + {u^2}}}{x \over {1 + {x^2}}} + {u \over {1 + {u^2}}}{1 \over {1 + {x^2}}} - {u \over {1 + {u^2}}}{1 \over {1 + xu}}$$

Now, integrating the first two terms, which account to the same$^1$, gives that you integral is

$$\mathcal I=\frac \pi 4\log 2-\int_0^1\int_0^1 \frac u {1+u^2}\frac{1}{1+xu}dxdu$$

Now, the latter integral is just our original integral, due to symmetry, as you see in $(1)$

This means that $$\mathcal I =\frac \pi 8 \log 2$$

as desired. $1$: symmetry, once again.

See here for a similar integral and its solution with double integrals.

Some insight about the two methods considered:

Note that as Sasha is showing

$$I(1)=\int_0^1 I'(a)da=\int_0^1 \int_0^1\frac{x}{(1+ax)(1+x^2)}dxda$$ which is exaclty what we got in the second option

$$I=\int_0^1\int_0^1 \frac{1 }{1+mx}\frac{x}{1+x^2}dxdm$$

This means any way you find to solve any of the two will indeed solve the other.

  • $\begingroup$ For other examples of the technique, please see this. $\endgroup$ – André Nicolas Jul 17 '12 at 20:31
  • $\begingroup$ @André Nicolas : Is it also possible to convert it into double integral and solve it ? $\endgroup$ – Theorem Jul 17 '12 at 20:38
  • $\begingroup$ @Theorem That should also work, and I also reccommend it. It should be an eigth of $\pi \log 2$. $\endgroup$ – Pedro Tamaroff Jul 17 '12 at 20:38
  • $\begingroup$ @PeterTamaroff : nice . $\endgroup$ – Theorem Jul 17 '12 at 20:48

I solved this integral a couple of years ago and I had this solution typed out in $\LaTeX$ already. The solution is not conventional, so I think it's worth sharing!

First, substitute the series $$\log(1+x)=\sum_{n=1}^\infty \frac{(-1)^{n-1}x^n}{n}.$$

This series is uniformly convergent on $[0,1]$, so we can interchange the sum and the integral. We get

$$I=\sum_{n=1}^\infty \frac{(-1)^{n-1}}{n} \int_0^1 \frac{x^n}{1+x^2}\: \mbox{d}x. = \sum_{n=1}^\infty \frac{(-1)^{n-1}}{n}C_n$$

where $$C_n=\int_0^1 \frac{x^n}{1+x^2} \mbox{d}x.$$

Now since $$x^{n-2}-\frac{x^{n-2}}{1+x^2}=\frac{x^n}{1+x^2},$$

we have, integrating this equation on $[0,1]$, $$\frac{1}{n-1}-C_{n-2}=C_n.$$ Hence we have a recurrence relation for the $C_n$'s. Let's see what this gives. We have $$C_0=\int_0^1 \frac{ \mbox{d}x}{1+x^2} = \arctan(1) = \frac{\pi}{4},$$ and

$$C_1=\int_0^1 \frac{x\ \mbox{d}x}{1+x^2} = \frac{1}{2}\log2.$$

Now using the recurrence we find





$C_4 = -1+\frac{1}{3} +\frac{\pi}{4}$

$C_5=-\frac{1}{2}+\frac {1}{4} +\frac{1}{2}\log 2$

$C_6=1-\frac{1}{3}+\frac{1}{5} - \frac{\pi}{4}$


Now if we define

$$A_n = \sum_{k=1}^n\frac{(-1)^{k-1}}{2k},$$ $$B_n = \sum_{k=1}^n\frac{(-1)^{k-1}}{2k-1},$$ it is easy to see by induction that $$C_{2n} = (-1)^n\left(\frac{\pi}{4}-B_n\right)$$ and

$$C_{2n-1} = (-1)^{n-1}\left(\frac{\log 2}{2} -A_{n-1}\right).$$

Notice that $A_n \rightarrow \frac{1}{2}\log2$ as $n\rightarrow \infty$ [recall the series expansion of $\log(1+x)$], and that $B_n \rightarrow \frac{\pi}{4}$ as $n\to \infty$ [recall the series expansion of $\arctan x$, which you can get by integrating $(1+x^2)^{-1}$].

Let us examine the partial sums

$$I_{2N}=\sum_{n=1}^{2N} \frac{(-1)^{n-1}}{n}C_n.$$

We can split this into the odd-labeled terms and the even-labeled terms, as

$$I_{2N}= \sum_{n=1}^{N} \frac{C_{2n-1}}{2n-1} - \sum_{n=1}^{N} \frac{C_{2n}}{2n}.$$

Now we can substitute the values of $C_{2n}$ and $C_{2n-1}$ obtained before. First, let us look at the sum of the even-labeled terms. We have

$$\sum_{n=1}^{N} \frac{C_{2n}}{2n} =\sum_{n=1}^{N} \frac{ (-1)^{n}}{2n}\left(\frac{\pi}{4}-B_n\right)=-\frac{\pi}{4}A_N +\sum_{n=1}^N\frac{(-1)^{n-1}}{2n}B_n $$

Now let us recall Cauchy's partial summation formula. For sequences $\{a_n\}, \{b_n\}$, we denote $\{\Delta a_n\}$ the sequence of forward differences $\Delta a_n = a_{n+1}-a_n$. Then we have

$$\sum_{n=1}^N b_n \Delta a_{n-1} = b_Na_N - b_1a_0 -\sum_{n=1}^{N-1} \Delta b_n a_n.$$

Remark that $\Delta A_{n-1} = \frac{(-1)^{n-1}}{2n}$. Also, $A_0=0$. Hence,

$$-\frac{\pi}{4}A_N +\sum_{n=1}^N\Delta A_{n-1}B_n = -\frac{\pi}{4}A_N +B_NA_N -\sum_{n=1}^{N-1}\Delta B_n A_n.$$

(Call this sum (1)).

Now we go back to the sum of the odd-labeled terms. We have, in a similar fashion,

$$\sum_{n=1}^{N} \frac{C_{2n-1}}{2n-1} = \sum_{n=1}^{N} \frac{(-1)^{n-1}}{2n-1}\left(\frac{\log 2}{2} - A_{n-1}\right) = \frac{\log 2}{2} B_N - \sum_{n=1}^N \Delta B_{n-1}A_{n-1}$$ $$= \frac{\log 2}{2} B_N - \sum_{n=0}^{N-1} \Delta B_{n}A_{n}.$$ (Call this sum (2)).

Now, subtracting (1) from (2), we get

$$I_{2N} = \frac{\log 2}{2}B_N + \frac{\pi}{4}A_N - B_NA_N +\Delta B_0 A_0$$ $$= \frac{\log 2}{2}B_N + \frac{\pi}{4}A_N - B_NA_N$$

Now as $N\to \infty$, since $A_N \to \frac{1}{2}\log 2$ and $B_N \to \frac{\pi}{4}$, we have

$$I = \int_0^1\frac{\log(1+x)}{1+x^2}\: \mbox{d}x = \lim_{N\to \infty} I_{2N} = \frac{\pi \log 2}{8}.$$


$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ \begin{align} \color{#00f}{\large\int_{0}^{1}{\ln\pars{1 + x} \over 1 + x^{2}}\,\dd x}& =\int_{0}^{\pi/4}\ln\pars{1 + \tan\pars{\theta}}\,\dd\theta \\[3mm]&=\half\bracks{% \int_{0}^{\pi/4}\ln\pars{1 + \tan\pars{\theta}}\,\dd\theta + \int_{0}^{\pi/4}\ln\pars{1 + \tan\pars{{\pi \over 4} - \theta}}\,\dd\theta} \\[3mm]&=\half\bracks{% \int_{0}^{\pi/4}\ln\pars{1 + \tan\pars{\theta}}\,\dd\theta + \int_{0}^{\pi/4}\ln\pars{% 1 + {1 - \tan\pars{\theta} \over 1 + \tan\pars{\theta}}}\,\dd\theta} \\[3mm]&=\half\bracks{% \int_{0}^{\pi/4}\ln\pars{1 + \tan\pars{\theta}}\,\dd\theta + \int_{0}^{\pi/4}\ln\pars{2\over 1 + \tan\pars{\theta}}\,\dd\theta} \\[3mm]&=\half\int_{0}^{\pi/4}\ln\pars{2}\,\dd\theta =\color{#00f}{\large{1 \over 8}\,\pi\ln\pars{2}} \end{align}

  • $\begingroup$ @JeffFaraci Thanks a lot. $\endgroup$ – Felix Marin Jul 1 '17 at 21:45

$\displaystyle A=\int_0^1\dfrac{\Big(\log(1+x)\Big)^2}{1+x^2}dx$

Perform the change of variable $y=\dfrac{1-x}{1+x}$

$\displaystyle A=\int_0^1\dfrac{\left(\log\left(\dfrac{2}{1+x}\right)\right)^2}{1+x^2}dx=\int_0^1\dfrac{\Big(\log 2-\log(1+x)\Big)^2}{1+x^2}dx$

$\displaystyle A=\int_0^1\dfrac{\Big(\log 2\Big)^2}{1+x^2}dx-2\int_0^1\dfrac{\log 2\log(1+x)}{1+x^2}dx+A$


$\displaystyle \int_0^1\dfrac{2\log 2\log(1+x)}{1+x^2}dx=\int_0^1\dfrac{\Big(\log 2\Big)^2}{1+x^2}dx$


$\displaystyle \int_0^1\dfrac{\log(1+x)}{1+x^2}dx=\int_0^1\dfrac{\log 2}{2(1+x^2)}dx=\dfrac{\log 2}{2}\Big[\arctan x\Big]_0^1=\dfrac{\pi\log 2}{8}$

  • $\begingroup$ (+1) Nice. How did you come up with this? $\endgroup$ – joriki Jun 14 '16 at 0:05
  • $\begingroup$ It's a stuff you're regularly rediscovering when playing with such integrals. At the moment, i'm trying to give an evaluation (in terms of usual constants and special valules of well-known functions) of the integral named A above. $\endgroup$ – FDP Jun 14 '16 at 6:20
  • 1
    $\begingroup$ Actually, one can simplify the computation. Perform directly the change of variable $y=\dfrac{1-x}{1+x}$ in the requested integral. $\endgroup$ – FDP Jun 14 '16 at 17:12
  • $\begingroup$ The simplified computation above is a worthy answer on its own. I found it the simplest among the methods on this page. $\endgroup$ – Rahul Madhavan Dec 28 '18 at 9:47

For these integrals are very useful substitutions homograph type.

To note $\displaystyle I(a) = \int^{a}_{0}\frac{\ln(x+a)}{x^{2}+a^2}dx.$

Using the substitution $x=\dfrac{-at+a^2}{t+a} = u(t)$ with $u'(t)=-\dfrac{2a^2}{(t+a)^2} $ we find $$\begin{align*}I(a) &= \int^{0}_{a}\frac{\ln\left(\frac{-at+a^2}{t+a}+a\right)}{\left(\frac{-at+a^2}{t+a}\right)^2+a^2}\left(- \frac{2a^2}{(t+a)^2}\right)dt=\\ &= \int^{a}_{0}\frac{\ln 2a^2 - \ln(t+a)}{t^2+a^2}dt = \\ &=\int^{a}_{0}\frac{\ln 2a^2}{t^2+a^2}dt -\int^{a}_{0}\frac{\ln(t+a)}{t^2+a^2}dt=\\ & =\frac{\ln2a^{2}}{a} \arctan 1- I(a).\end{align*}$$

And finally $$I(a) = \dfrac{\pi}{8}\cdot\frac{\ln2a^{2}}{a}.$$ For $ a= 1$ we obtain $I(1) = \dfrac{\pi}{8}\ln2.$

See also: http://www.recreatiimatematice.ro/arhiva/articole/RM12011DICU.pdf

  • $\begingroup$ I edited your answer. If you are interesting in $TeX$ code you can see it clicking on edit button. For some basic information about writing math at this site see e.g. here, here, here and here. And nice answer! (+1) $\endgroup$ – Cortizol Jun 29 '13 at 20:13
  • $\begingroup$ medicu - Small error in your final answer for $I(a)$. It should be $I(a) = \frac{\pi \ln (2a^2)}{8 a}$. $\endgroup$ – omegadot Feb 23 '16 at 1:46
  • $\begingroup$ Thank you very much! I corrected. $\endgroup$ – medicu Feb 25 '16 at 11:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.